Developing Post-Primary Education in Sub-Saharan Africa : Assessing the Financial Sustainability of Alternative Pathways - Mingat, Alain (World Bank, 2012)
All countries in Sub-Saharan Africa (SSA) face the prospect of a substantial increase in the number of primary school completers in the coming years. Although initial conditions vary widely from country to country, this increase will inevitably intensify pressure on the education system, particularly at the secondary and tertiary levels. African countries may thus find it timely to align their education policies and strategies to the emerging challenges. A key goal is to ensure that the education system continues to develop in an efficient, equitable, and fiscally sustainable manner even as it expands to accommodate the rising numbers seeking a place in secondary and tertiary education. The rest of this report is organized as follows. Chapter two elaborates the policy context for education development in SSA. Chapter three explains the methodology and data sources. Chapter four examines the challenges and constraints posed by the sheer volume of increases in enrollments in post-primary education with which most education systems in SSA must grapple in the coming years. Taking these constraints into account, the report evaluates the scope for policy development from three perspectives in the subsequent chapters: the coverage of education systems (chapter five), the quality and cost of service delivery (chapter six), and the division of financing by public and private sources (chapter seven). The fiscal implications of plausible policy packages that SSA countries might consider are assessed in chapter eight. Chapter nine seems up the general conclusions of the report.